The Relationship between Student Creativity and Accounting Learning Outcomes of Accounting Department Students of SMK Negeri 21 Jakarta - shofiany, shofiany (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
Law Number 20 of 2003 regulating the National Education System serves as the basis for regulations governing education in Indonesia. The curriculum implemented in Indonesia is always being updated and improved according to community needs. At school children are trained to only look for one answer to a problem. Answers must be single and uniform, according to what the teacher wants. The creativity achieved by students after participating in accounting learning activities is generally used as a parameter for success in learning accounting itself. Until now, the condition of accounting teaching is not as expected, criticism and highlights are still being expressed Creativity in good accounting teaching and learning means that teachers must be able to create an atmosphere that makes students enthusiastic about the problem. Teachers need to help activate students to think, because basically teachers are facilitators who encourage students to learn independently as best as possible. In this case, it also plays a role as a consultant in helping students plan activities and teachers should be able to accept differences between students in their ability to think of new ideas and in the speed of completing assignments given by their teacher